Current Strategies for Noise Reduction in Hearing Aids - A Review - Abraham, Ajish K; T.E., Abhisheka; N, Manohar (Journal of All India Institute of Speech and Hearing, 2017)
Hearing the desired sound in presence of noise is the biggest challenge faced by a hearing aid user and hence is an area of great concern for the hearing aid designers as well as professionals. This paper reviews the noise reduction strategies currently implemented in hearing aid as well as those in the experimental stage with an objevtive to precipitate the concerns and provide a clear direction to the developments further required. Techniques used for noise reduction in hearing aid are classified into two : noised reduction using microphones and the noise reduction through digital signal processing techniques. Noise reduction using two omin directional microphones, three omni directional microphones and adaptive beamforming techniques were reviewed under the first category . In the second category, signal processing techniques such as Wavelet Based noise reduction. Blind Source Separation, Modulation Based Digital Noise Reducation. Multichannel Wiener Filter and Scene Analysis method were reviewed. ON Comparison, adaptive beamforming technique was found to be the most efficient one among the microphone based noise reduction strategies. Wavelet based noise reduction and scene Analysis method were found to be the better signal processing techniques.